HAK PREOGRATIF PRESIDEN DALAM MENGANGKAT KAPOLRI DITINJAU DARI SISTEM KETATANEGARAAN INDONESIA (JURNAL HUKUM SEHASEN, 2015)
Presidential system is a centralized system of governance on the powers of the President as head of government and head of the Country is in this system, the executive branch more robust in the face of a Presidential system rated entity legislatif.Keberadaan advantages and kekurangannya.Kelebihannya is that more presidential system guarantees the stability of governments, whereas the shortcomings, these systems tend to put the executive power as a part that is very influential because of his considerable powers besar.merupakan prerogative of the executive branch without the consent of any other party, to carry out certain activities or to provide or not provide specific consent solely if he considered itself is considered appropriate to do, with or without the recommendation of others. Indonesian Police Being under President executive powers and headed by the President as head of state and head of government, the National Police under Article 30 UUD 1945 is a tool of the state and not a tool of government as perceived in the pre-democratic system of government. The provisions of the 1945 Constitution in Article 301 paragraph 4 for very obvious Police confirmed it. Constitutionally, Police today, is a tool of the state, so that its position as a subordinate to the President, is associated with the notion of President as head of state, not in the context of the head and government functions in the technical sense. Seeing the advantages and disadvantages of the presidential system, especially in the case of the appointment of the leader of the state apparatus, then the necessary constitutional arrangements to finance the negative impact or weakness of the system in Keywords: Presidential System, Prerogatives Rights, Police Chief Appointment